Praktik Pemanggilan Arwah Orang Mati dalam Tradisi Suku Batak Toba: Tinjauan Teologis Berdasarkan 1 Samuel 28:7 - Natanael, Rafael; Pane, Exson Eduaman (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This research examines the practice of necromancy among the Toba Batak from a theological perspective, specifically based on 1 Samuel 28:7. This practice, although it has long been an integral part of Batak culture, poses serious challenges when confronted with the teachings of the Christian faith. In the present context, there are still Batak Christian communities who practice this ritual as a form of respect for ancestors, even though the Bible explicitly opposes it. This research uses a qualitative method with a literature study approach to trace the roots of this belief, exegetical analysis of 1 Samuel 28:7, and the church's response to this phenomenon. The results show that there is syncretism between Christian teachings and local culture that causes theological confusion among the congregation. This finding indicates the need for a contextualized and educative pastoral approach by the church in guiding people to uphold the Christian faith without completely abandoning their cultural identity. This research emphasizes the importance of churches understanding the local cultural context in conveying doctrine and developing relevant and transformative mission strategies.